2022
DOI: 10.1002/smll.202203510
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Strained B‐Doped Ni Nanoparticles for Efficient Electrochemical H2O2 Synthesis

Abstract: Surface strains are necessary to optimize the oxygen adsorption energy during the oxygen reduction reaction (ORR) in the four‐electron process, but the surface strains regulation for ORR in the two‐electron process to produce hydrogen peroxide (H2O2) is rarely studied. Herein, it is reported that the tensile strained B‐doped Ni nanoparticles on carbon support (Ni‐B@BNC) could enhance the adsorption of O2, stabilize OO bond, and boost the electrocatalytic ORR to H2O2. Moreover, the Ni‐B@BNC catalysts exhibit v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…proved that the compressive strain between core and shell regions could cause a downshift of the d‐band center of Pd sites, thus achieving high ORR activity [20] . Moreover, we also found that the tensile‐strained B‐doped Ni nanoparticles on carbon support (Ni‐B@BNC) could enhance the adsorption of O 2 , stabilize O−O bond, and boost the electrocatalytic ORR to H 2 O 2 [21] . Besides, as a kind of three‐dimensional (3D) porous materials, metallic aerogels (MAs) have attracted much attention by reason of the large specific surface area and abundant interconnected channels.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…proved that the compressive strain between core and shell regions could cause a downshift of the d‐band center of Pd sites, thus achieving high ORR activity [20] . Moreover, we also found that the tensile‐strained B‐doped Ni nanoparticles on carbon support (Ni‐B@BNC) could enhance the adsorption of O 2 , stabilize O−O bond, and boost the electrocatalytic ORR to H 2 O 2 [21] . Besides, as a kind of three‐dimensional (3D) porous materials, metallic aerogels (MAs) have attracted much attention by reason of the large specific surface area and abundant interconnected channels.…”
Section: Introductionmentioning
confidence: 53%
“…[20] Moreover, we also found that the tensile-strained B-doped Ni nanoparticles on carbon support (Ni-B@BNC) could enhance the adsorption of O 2 , stabilize OÀ O bond, and boost the electrocatalytic ORR to H 2 O 2 . [21] Besides, as a kind of three-dimensional (3D) porous materials, metallic aerogels (MAs) have attracted much attention by reason of the large specific surface area and abundant interconnected channels. Thanks to the intrinsic physicochemical characteristics, MAs possess copious active sites, excellent structural durability and plentiful mass/electron transfer channels, endowing their widely applications in diverse electrocatalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The projected densities of states (PDOS) of the d -band in the Co atom of CoAl 2 O 4 and Co 3 O 4 are shown in Figure S12. The portion of CoAl 2 O 4 that occupies the d orbital (especially d z 2 ) is closer to the Fermi level than Co 3 O 4 . , The d z 2 orbital of cobalt can overlap with the p z orbital of oxygen to form a strong σ-bond, which is attributed to the spatial configuration of the d orbitals. , Therefore, the σ bond contributed by the Co d z 2 orbital of CoAl 2 O 4 improves the adsorption and desorption of OOH* and carries out effective 2-electron reduction. The densities of states shown in Figure d for CoAl 2 O 4 and Co 3 O 4 indicate that the Lewis acid site Al changes the density of states of the Co-3d orbital near the Fermi level. ,, Compared with the Co 3 O 4 (−3.06 eV), the d-band center of CoAl 2 O 4 (−2.78 eV) is closer to the Fermi level, which may enhance the adsorption of O 2 …”
Section: Resultsmentioning
confidence: 99%
“…Figure 4c 44,46 The dz 2 orbital of cobalt can overlap with the p z orbital of oxygen to form a strong σ-bond, which is attributed to the spatial configuration of the d orbitals. 47,48 52,53 This reveals that the addition of Lewis acid site Al can make the 2-electron ORR process in the cobalt catalytic active site become spontaneous reaction, which is conducive to the progress of ORR. When U = 0.7 V vs RHE, the ΔG *OOH (−0.…”
Section: ■ Introductionmentioning
confidence: 97%
“…Hydrogen peroxide (H 2 O 2 ) is widely used in many fields such as chemical synthesis, biology, medical treatment, and environmental protection. Up to now, the industrial production of H 2 O 2 still heavily relies on the energy-intensive anthraquinone process, which requires large-scale infrastructure and complicated extraction/purification procedures. Moreover, direct synthesis from H 2 and O 2 would be accompanied by unnecessary side reactions and high explosion risks. , Therefore, it is of great significance to find green, effective, and safe synthetic pathways for H 2 O 2 production. Two-electron (2e – ) oxygen reduction reaction (ORR) is a promising process for the direct synthesis of H 2 O 2 under ambient conditions. However, 4e – ORR is thermodynamically more favorable than 2e – ORR, leading to the low selectivity for H 2 O 2 synthesis. It is necessary to develop an efficient and stable electrocatalyst to promote the implementation of the 2e – ORR pathway via the obstruction of the cleavage of the O–O bond. , …”
Section: Introductionmentioning
confidence: 99%